Nicotinic acetylcholine receptor (CHRN) expression and function in cultured human adult fungiform (HBO) taste cells - Qian, Jie; Mummalaneni, Shobha; Larsen, James; Grider, John R.; Spielman, Andrew I.; Özdener, Mehmet Hakan; Lyall, Vijay (PLOS ONE, 2018)
In rodents, CHRNs are involved in bitter taste transduction of nicotine and ethanol. Currently, it is not clear if CHRNs are expressed in human taste cells and if they play a role in transducing the bitter taste of nicotine and ethanol or in the synthesis and release of neurohumoral peptides. Accordingly, we investigated the expression and functional role of CHRNs in HBO cells. Using molecular techniques, we demonstrate that a subset of HBO cells express CHRNs that also co-express TRPM5, T1R3 or T2R38. Exposing HBO cells to nicotine or ethanol acutely or to nicotine chronically induced a differential increase in the expression of CHRN mRNA and protein in a dose- and time-dependent manner. Acutely exposing HBO cells to a mixture containing nicotine plus ethanol induced a smaller increase in CHRN mRNAs relative to nicotine or ethanol treatment alone. A subset of HBO cells responded to nicotine, acetylcholine and ATP with a transient increase in [Ca2+]i. Nicotine effects on [Ca2+]i were mecamylamine sensitive. Brain-derived neurotrophic factor (BDNF) protein was detected in HBO cells using ELISA. Acute nicotine exposure decreased BDNF in HBO cells and increased BDNF release in the medium. CHRNs were also detected in HEK293 cells by RT-PCR. Unlike HBO cells, CHRNs were localized in most of HEK293 cells and majority of HEK293 cells responded to nicotine and ethanol stimulation with a transient increase in [Ca2+]i. BDNF levels in HEK293 cells were significantly higher than in HBO cells but the nicotine induced release of BDNF in the media was a fraction of the BDNF cellular content. We conclude that CHRNs are expressed in TRPM5 positive HBO cells. CHRN mRNA expression is modulated by exposure to nicotine and ethanol in a dose- and time-dependent manner. Nicotine induces the synthesis and release of BDNF in HBO cells.